Analisis Kelayakan Isi Buku Teks Wursita Basa Kelas IX SMP - Padmawati, Anggita Dwi; Suhita, Raheni; Veronika, Prima (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2024)
AbstrackThis research aims to describe the feasibility of the contents of the Javanese Wursita Basa textbook for class IX SMP/SMPLB/MTs published by CV. Friends This research uses a qualitative descriptive approach. Data analysis techniques use interactive analysis, namely data collection, data reduction, data presentation, and drawing conclusions. Content feasibility data and language feasibility are analyzed with instruments compiled based on relevant theories and information and assessments from several sources. Data validity test using researcher and theory triangulation. In triangulation, researchers involved other researchers, namely Dewinta Enha Putri (DEP). Content eligibility is reviewed from the appropriateness of the material, accuracy of the material, and the content of the learning material, while language eligibility is reviewed from the appropriateness of the language with the level of development of the students, communicative, as well as the sequence and unity of ideas. From the results of the analysis, it can be concluded that the feasibility of the content of the Wursita Basa Javanese textbook obtained a percentage of 79.6% from the average score of 25.5 and a maximum score of 32Keywords: textbook, contents feasibility, curriculum of 2013